An intelligent routing protocol in VANET. (2018) - Samara, Ghassan
Vehicular ad hoc networks (VANET) is one of the new promising and most challenging research area in the mobile computing field; this technology suffers from the high mobility which results in broken links and continuously changing routs. In this research, a new and Intelligent Routing Protocol (IRP) using position based proactive message transmission in VANET environment will be deployed. The proposed protocol aims to supply vehicles with live and quick information about the current links between road vehicles and hence better message routing, channel utilisation, error free, congestion free channel with less broken links using position based, multi-hop routing and best first search algorithm, simulation results show that the proposed protocol achieves better performance when compared with other protocols.